Diagnosis and treatment of cardiac iron overload in transfusion-dependent thalassemia patients - Natthaphat Siri-Angkul (2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Introduction: Thalassemia is among the most common genetic diseases. Patients with severe forms of the disease are transfusion-dependent, leading to iron overload. A condition which can eventually develop in the iron-loaded heart is iron overload cardiomyopathy, a debilitating disease that accounts for the majority of deaths in thalassemia patients. Areas covered: This review article provides a comprehensive summary of the diagnosis and treatment of cardiac iron overload in transfusion-dependent thalassemia patients, with discussion covering current weak points and potential improvements of the relevant diagnostic and therapeutic strategies. Expert commentary: Current limitations of various diagnostic techniques for iron overload cardiomyopathy include suboptimal accuracy, untimely detection, or inadequate accessibility, and novel modalities are required to overcome these shortcomings. Treatment should address key pathophysiologic mechanisms of iron overload cardiomyopathy, which include cardiac iron mishandling and iron-induced oxidative injury. Apart from the promotion of iron removal by chelators, prevention of cardiac iron deposition and attenuation of oxidative damage should also be rigorously investigated on a cell-to-bedside basis.